Design of Soybean Epidermis Peeler - Siska Willyana; Achwil Putra Munir; Adian Rindang (Universitas Sumatera Utara, 2015)
Soybean peeling is aimed to simplify the processing of soybean in the next step, such as in tofu making, tempe making and soybean extract. The peeling techniques of soybean was used widely with simple way which is soaked in the water and stomp it in a basin until its skin peeled. This research was to design, make, test and analyze the economic value of the soybean peeler. The parameters of this research were effective capacity, broken peeled soybean percentage, unpeeled soybean percentage, losses soybean percentage and economic analysis. The results showed the effective capacity was 55,5 kg/hour. Percentage of broken peeled soybean was 4,91%, percentage unpeeled soybean was 11,01% and percentage of losses soybean was 2,1%. Economic Analysis was Rp. 104,373/kg, BEP was 259,32 kg/year and IRR was 66,54%. Key words : epidermis, peeler, silinder type, soybean